OBESITY AND DIABETES AS DETERMINANTS OF VITAMIN D DEFICEIENCY. - Gilani, Syed Yasir Hussain; Bibi, Saima; Siddiqui, Afsheen; Shah, Syed Raza Ali; Akram, Faiza; ur Rehman, Mujeeb (Journal of Ayub Medical College Abbottabad, 2019)
Background: Vitamin D has been the focus of attention in the recent past owing to its multitude of effects on various organ systems including immune system, endocrine, cardiovascular etc. Diabetes mellitus and obesity are widely prevalent in our region. The present study was designed with an objective to determine the vitamin D status in relation to diabetes mellitus and obesity in our area. Methods: This cross-sectional study was conducted at the Medical C Unit of Department of Medicine, Ayub Teaching Hospital from January to December 2017. Approval of ethical committee was taken. A total of 117 patients were enrolled in this study of which 109 were finalized for analysis owing to incomplete data in 8 cases. Patients' characteristics were recorded on a structured proforma. Type 2 diabetes was confirmed using HbA1C Levels. Using ADA 2016 criteria. Vitamin D status was assessed using 25-OH-Vit D levels from the same laboratory. Height and weight of the patients were recorded to obtain BMI. Data was entered and analysed using SPSS version 20. Results: Of the total sample, 69 (63.3%) were females and 40 (36.7%) were males. Mean age of the participants was 44.13±15.777. Mean vitamin D levels were 26.35±18.72. A total of 83 (76.14%) patients were either vitamin D deficient 66 (60.6%) or insufficient 17 (15.6%) while 26 (23.9%) were sufficient in vitamin D. There was statistically significant difference in vitamin D status in diabetic versus non diabetic patients (p=0.015). As regards BMI and vitamin D status, the difference was also statistically significant (p=0.018). Conclusion: Vitamin D deficiency is widely prevalent in our region. There is also a high prevalence of obesity and diabetes mellitus and they are inversely related to low vitamin D levels. Keywords: Vitamin D deficiency; obesity; diabetes